1987
DOI: 10.1002/tcm.1770070310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal and fetal toxic dose responses in mammals

Abstract: The role of maternal toxicity in adverse developmental outcome and the importance of maternal toxicity as a factor in developmental risk assessment have received increasing attention in the recent literature. This paper reviews these concepts and some of the experimental approaches that have been used to assess their importance. The often non-parallel nature of maternal and fetal toxic dose response curves makes specific comparisons of maternal and fetal toxic doses quite difficult. The use of specific ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The experimental designs of these studies were quite inadequate to the stated goal of examining the predictability of A/D ratios across mammalian species because of the selection of submammalian endpoints. Other studies (Rogers, 1987;Rogers et al, 1988) reported that in response to the fungicide dinocap, the mouse had an A/D ratio of -16, whereas the rat and hamster had A/D ratios of 1 .…”
Section: ;mentioning
confidence: 98%
See 1 more Smart Citation
“…The experimental designs of these studies were quite inadequate to the stated goal of examining the predictability of A/D ratios across mammalian species because of the selection of submammalian endpoints. Other studies (Rogers, 1987;Rogers et al, 1988) reported that in response to the fungicide dinocap, the mouse had an A/D ratio of -16, whereas the rat and hamster had A/D ratios of 1 .…”
Section: ;mentioning
confidence: 98%
“…It is not surprising that doubts have been expressed concerning the constancy of the A/D ratio calculated across species (Daston and D'Amato, 1989;Daston et al, , 1991Rogers, 1987;Rogers et al, 1988;Schardein, 1987). However, good examples of different ratios for the same chemicals tested in standard evaluations are rare or nonexistent.…”
Section: ;mentioning
confidence: 99%